Interoperability between Ad-Financed Platforms with Endogenous Multi-Homing - Marc Bourreau; Adrien Raizonville; Guillaume Thébaudin (Center for Economic Studies and ifo Institute (CESifo), 2023)
Platform interoperability is considered a powerful tool to promote competition in digital markets when network effects are at play. We study the effect of interoperability on competition between two ad-financed platforms, allowing for endogenous multi-homing of consumers. When the platforms are symmetric and decide non-cooperatively on their level of interoperability, interoperability emerges in equilibrium if the value of multi-homers relative to single-homers is sufficiently low for advertisers. From a welfare perspective, the equilibrium level of interoperability can be either too low or too high. When one ("large") platform has an installed base of customers, its incentive to make its services interoperable is lower than for the other, smaller platform. However, mandating interoperability between the asymmetric platforms is not always socially optimal.
Keywords: L13; L86; L15; 330; interoperability; platform competition; multi-homing; advertising